The potency of spice extracts in fish skin collagen production - Sadi Nina Hermayani (EDP Sciences, 2021)
Spices can be used as an alternative washing agent in fish collagen production, replacing organic materials' commonly used washing agent. Many Asians, including Indonesian traditional culinary use spices to remove the fishy odor. Therefore this research was conducted to obtain a suitable spice used as a washing agent in fish collagen production. Ginger, galangal, lemongrass, bay leaves, lime leaves, and pandan leaves were used as the tested spices in the form of 5% liquid extract in water. The ANOVA and LSD test on fishy odor test data showed that most respondents preferred Pangasius skin soaked in galangal liquid extract and had no significant difference in odor compared to the control (ethanol). Pangasius skin soaked in galangal extract had the total protein and ash content lower than control, while the total fat and water content were higher. Soaking in galangal extract also made Pangasius skin have a higher degree in swelling and total protein content in its acid-soluble collagen (ASC) extract than in control. The higher value of the two latter parameters was also found in the descaling Tuna skin soaked in galangal extract.